1999
DOI: 10.1159/000017112
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Type and Severity of Dementia on Hospitalization and Survival of the Elderly

Abstract: We conducted a retrospective cohort study to examine whether patients with Alzheimer’s disease (AD) or vascular dementia (VaD) differed in the number and type of associated comorbid conditions. In addition, we evaluated the impact of the severity of cognitive impairment on hospitalization and mortality of patients in each group. We studied 161,106 patients over age 65, with any degree of cognitive impairment, residing in any of 1,573 Medicare/Medicaid-certified nursing homes of 5 states of the USA between 1992… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
4
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 51 publications
(68 reference statements)
4
30
4
2
Order By: Relevance
“…One reason for our findings could be related to the types of dementias and the comorbidities associated with them. As an example, patients with vascular dementia had the highest comorbidity scores, related to conditions associated with cardiovascular risk: hypertension, hyperlipidemia, stroke, peripheral vascular disease and others [36][37][38][39] Table 5: Unadjusted and adjusted cox proportional hazard ratios for in-hospital Dementia mortality by nis year and age group: african americans, hispanics vs. whites*.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for our findings could be related to the types of dementias and the comorbidities associated with them. As an example, patients with vascular dementia had the highest comorbidity scores, related to conditions associated with cardiovascular risk: hypertension, hyperlipidemia, stroke, peripheral vascular disease and others [36][37][38][39] Table 5: Unadjusted and adjusted cox proportional hazard ratios for in-hospital Dementia mortality by nis year and age group: african americans, hispanics vs. whites*.…”
Section: Discussionmentioning
confidence: 99%
“…It was not possible to classify dementia by subtype for decedents, so rates of VaD amongst decedents were estimated by applying the same relative increase in age-sex rates obtained for dementia in general. This may still be an underestimation due to the imperfect sensitivity of the approach [6] and since survival from VaD is less than that from AD [12]. With the inclusion of decedents, the global incidence rate rose to 3.79 per 1,000 undemented Canadians.…”
Section: The Incidence Of Vad In the Cshamentioning
confidence: 99%
“…Today we know that dementia shortens life [1,2,3] but also that there is a notable individual variability in the clinical course and no reliable prognostic tool predicting the length of survival or a fast cognitive decline. Many studies have tried to explore potential risk factors for the survival rate and rapid disease progression [4,5,6,7]. For example, Magierski et al [8] found that diabetes and hypertension influenced survival in AD but not in DLB.…”
Section: Introductionmentioning
confidence: 99%